2022
DOI: 10.1097/cce.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

In COVID-19 Patients Who Suffer In-Hospital Cardiac Arrest, Cardiopulmonary Resuscitation Outcomes May Be Impacted by Arrest Etiology and Local Pandemic Conditions

Abstract: OBJECTIVES: The utility and risks to providers of performing cardiopulmonary resuscitation after in-hospital cardiac arrest in COVID-19 patients have been questioned. Additionally, there are discrepancies in reported COVID-19 in-hospital cardiac arrest survival rates. We describe outcomes after cardiopulmonary resuscitation for in-hospital cardiac arrest in two COVID-19 patient cohorts. DESIGN: Retrospective cohort study. SETTING: New York-Presbyterian Hospital/Columbia University Irving Medical Center in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The pandemic has highlighted the importance of implementing do-not-resuscitate (DNR) orders for hospitalized patients who are at high risk of decompensation; this is particularly salient for COVID-19 inpatients with COVID-19 who suffer cardiac arrest, given the low survival rates observed among those given CPR. 59,60 In situations where direct knowledge of the patient's goals of care is not available, physicians require expert opinions and guidance. It is still unclear if incorporation biomarkers such as neuron-specific enolase, electrophysiology such as electroencephalographic reactivity, imaging tools such as diffusion-weighted magnetic resonance imaging (DWI), or algorithms to increase the accuracy of decisions in COVID-19 patients will be helpful.…”
Section: Consider Resuscitation Appropriatenessmentioning
confidence: 99%
“…The pandemic has highlighted the importance of implementing do-not-resuscitate (DNR) orders for hospitalized patients who are at high risk of decompensation; this is particularly salient for COVID-19 inpatients with COVID-19 who suffer cardiac arrest, given the low survival rates observed among those given CPR. 59,60 In situations where direct knowledge of the patient's goals of care is not available, physicians require expert opinions and guidance. It is still unclear if incorporation biomarkers such as neuron-specific enolase, electrophysiology such as electroencephalographic reactivity, imaging tools such as diffusion-weighted magnetic resonance imaging (DWI), or algorithms to increase the accuracy of decisions in COVID-19 patients will be helpful.…”
Section: Consider Resuscitation Appropriatenessmentioning
confidence: 99%
“… [10] , [11] However, over the last year, subsequent studies from the United States have demonstrated a 14.6-22.4% survival to discharge after COVID-19 IHCA. [12] , [13] …”
Section: Introductionmentioning
confidence: 99%